In-Process Recycling of 35% Glass Fiber-Reinforced Polyamide 6,6 Runners: Effects on Thermomechanical Properties and Viability for Diesel Injector Socket Production - Sahiner, Elif; Altin, Yasin (Mdpi, 2025)
Significant pre-consumer waste in the form of runners is generated during the injection molding of high-performance automotive components, representing both a substantial economic loss and an environmental burden. This study therefore comprehensively evaluated the mechanical recycling of pre-consumer 35% glass fiber-reinforced Polyamide 6,6 (%35GF-PA66) runners for in-process reuse in diesel injector socket production. The effects of blending recycled polymer (RP) at 2.5%, 5%, 10%, and 15% by weight and up to 10 recycling cycles with 15 wt.% RP on the thermal, mechanical, and morphological properties were investigated. Tensile strength slightly decreased (similar to 3% at 10% RP) compared to virgin material, while elongation at break increased with higher RP content. Multiple recycling cycles had minimal impact on tensile strength, and the heat deflection temperature (HDT) remained nearly constant (similar to 0.7 degrees C variation after 10 cycles, within experimental uncertainty). The melt flow index (MFI) increased significantly with successive recycling cycles, indicating molecular weight reduction due to thermomechanical degradation. DSC analysis confirmed stable melting and crystallization temperatures (variation < 1 degrees C), suggesting preserved crystalline structure. SEM analysis revealed increased void formation at the fiber-matrix interface and fiber attrition with successive recycling, correlating with reduced flexural properties. In-process recycling of %35GF-PA66 runners is viable, particularly at <= 15% RP and fewer cycles, offering significant cost savings (e.g., similar to EUR 344,000 annually for a large producer) and environmental benefits.
Keywords: circular economy; glass fiber composites; in-process reuse; mechanical recycling; Polyamide 6,6; sustainable manufacturing